Risk factors for excess deaths during lockdown among older users of secondary care mental health services without confirmed COVID‐19: A retrospective cohort study. (19th August 2021) - Chen, Shanquan; Jones, Peter B.; Underwood, Benjamin R.; Fernandez‐Egea, Emilio; Qin, Pei; Lewis, Jonathan R.; Cardinal, Rudolf N.
Abstract: Objective: To investigate factors contributing to excess deaths of older patients during the initial 2020 lockdown beyond those attributable to confirmed COVID‐19. Methods: Retrospective cohort study comparing patients treated between 23 March 2020 and 14 June 2020, deemed exposed to the pandemic/lockdown, to patients treated between 18 December 2019 and 10 March 2020, deemed to be unexposed. Data came from electronic clinical records from secondary care mental health services in Cambridgeshire and Peterborough NHS Foundation Trust (CPFT), UK (catchment area population ∼0.86 million). Eligible patients were aged 65 years or over at baseline with at least 14 days' follow‐up, excluding patients diagnosed with confirmed or suspected SARS‐CoV‐2 infection. The primary outcome was all‐cause mortality. Findings: In the two cohorts, 3, 073 subjects were exposed to lockdown and 4, 372 subjects were unexposed; the cohorts were followed up for an average of 74 and 78 days, respectively. After controlling for confounding by sociodemographic factors, smoking status, mental comorbidities, and physical comorbidities, patients with dementia suffered an additional 53% risk of death (HR = 1.53, 95% CI = 1.02–2.31), and patients with severe mental illness suffered an additional 123% risk of death (HR = 2.23, 95% CI = 1.42–3.49). No significant additional mortality risks were identified from physical comorbidities, potentially due to low statistical power in that respect. Conclusion: During lockdown people with dementia or severe mental illness had a higher risk of death without confirmed COVID‐19. These data could inform future health service responses and policymaking to help prevent avoidable excess death during future outbreaks of this or a similar infectious disease. Key points: Previous studies have explored the risk factors for death following COVID‐19 infection, but data regarding the totality of excess deaths is sparse We conducted a retrospective cohort study based on a large clinical record database, making a comparison with a historical control group We found that older people with dementia or serious mental illness had a higher risk of death without confirmed COVID‐19 under the circumstance of lockdown This study could have an impact on existing health systems and clinical practice in response to the excess death associated with COVID‐19 lockdown, and inform preparation for possible future outbreaks